(untitled) (Plant Tissue Culture and Biotechnology, 2011)
The effect of external BAP on explants including leaflets, stems, cotyledons with and without embryo axis of lentil (Lens culinaris Medic.) were tested on the frequency of shoot induction. The effect of different levels and combinations of various cytokinins on multiple shoot induction and elongation of shoots were compared. The effect of explant age and pH of media were also tested on shoot induction from various explants. Finally, the effect of IBA, IAA, and NAA on root induction of elongated shoots were examined. Optimum conditions for root emergence and growth and the hardening of seedlings were determined. Cotyledon with small part of the embryo axis was the superior explant. Shoot induction from the explants was enhanced by inclusion of BAP in the seed germination medium. The highest shoot induction (up to 96%) was obtained on MS with 7.5 µM 2-ip, 4 µM kn, and 2 µM TDZ. Over 80% of the elongated shoots produced roots in solid 1/4 BS media with 50 µM NAA for 3 days followed by 10 days in a mixture of liquid 1/4 BS, vermiculite and sand. Root development and hardening of the seedlings was achieved by using a hydroponics system containing Arnons solution. Tissue culture derived plants were transplanted to the greenhouse where the seeds were harvested after about 4 months. Key words: regeneration, Cotyledon, Embryo axis, Lentil, Lens culinaris D. O. I. 10.3329/ptcb.v21i2.10240 Plant Tissue Cult. & Biotech. 21(2): 169-180, 2011 (December)